2016
DOI: 10.1016/j.jiph.2015.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Association of bacteria in diabetic and non-diabetic foot infection – An investigation in patients from Bangladesh

Abstract: The microbial community on a host relies on its immune status and pathophysiological condition. Diabetes mellitus is a metabolic disorder associated with a 25% increased risk of developing foot infection. The pathophysiological differences between diabetic foot infection (DFI) and non-DFI patients may alter the microbial composition in infections. The present study aims to comparatively analyze the microbes colonized in DFI and non-DFI patients in Bangladesh. Pus specimens were collected from 67 DFI and 12 non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 22 publications
7
29
1
2
Order By: Relevance
“…(22/7%), and Staphylococcus spp. (13/13%) [32]. Furthermore, in a study performed in India, Gram-negative pathogens were reported to be the most predominant (58.5%) [31], thereby demonstrating the prevalence of Gram-negative bacteria in Eastern countries.…”
Section: Microbiota In Dfusmentioning
confidence: 94%
See 3 more Smart Citations
“…(22/7%), and Staphylococcus spp. (13/13%) [32]. Furthermore, in a study performed in India, Gram-negative pathogens were reported to be the most predominant (58.5%) [31], thereby demonstrating the prevalence of Gram-negative bacteria in Eastern countries.…”
Section: Microbiota In Dfusmentioning
confidence: 94%
“…Openly published evidence suggests that there is no reason to prescribe antibiotic therapy for an uninfected foot wound as either a prophylaxis against infection or in the belief that it accelerates the healing of the wound [36]. In a study performed in Bangladesh, most of the isolates from DFI patients were commonly resistant to cephalosporin (ceftazidime, ceftriaxone, cefuroxime) and carbapenem (aztreonam) [32]. In Mexico, the least effective antibiotics for Gram-positive bacteria identified in DFIs were penicillin and dicloxacillin; for Gram-negative bacteria, cefalotin and penicillin were the least effective.…”
Section: Multidrug-resistant Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…A report is presented here concerning association of multidrug-resistant (MDR) clinical P. stutzeri 40D2 (initially named as 40/D/Mac2) isolated from the pus sample of a diabetic patient with a deep tissue foot infection (cellulitis) in a tertiary care hospital in Dhaka, Bangladesh. 9 Initially, 20 isolates were recovered among which three carbapenem resistant Pseudomonas isolates (40/D/Mac2, 40/D/Swab1, 40/D/CIP+Cefo1) were retrieved belonging to a single genotype, detected through amplified ribosomal DNA restriction analysis. Isolate 40D2 was selected for detailed investigation.…”
mentioning
confidence: 99%